Effects of precocenes on ovarian development of the seed bug, Oxycarenus lavaterae (F.) (Revista Española de Fisiología, 1986)
Antigonadotropic activities of Precocene 1 (P1), Precocene 2 (P2) and Ethoxyprecocene 2 (EP2) on the seed bug Oxycarenus lavaterae (F.) (Heteroptera, Lygaeidae), are reported.EP2 proved to be the most active compound followed by P2 and P1, which agrees with the structure-activity relationships reported for these compounds thus far.Mortality in both sexes was furthermore studied.In this context, compound P2 showed the highest degree of toxicity.Males, interestingly, appeared to be more sensitive to the toxic effects of Precocenes.